Prevalence of residual limb pain and symptomatic neuromas after lower extremity amputation: a systematic review and meta-analysis. Issue 7 (July 2021) - List, Emile B.; Krijgh, David D.; Martin, Enrico; Coert, J. Henk
Abstract : Abstract: Residual limb pain (RLP) is associated with (partial) extremity amputations and is defined as pain felt in the remaining part of the amputated limb. A common cause of RLP is neuroma formation after nerve transections. Neuromas can be very painful and severely debilitating pathologies, preventing prosthetic use, reducing quality of life, and requiring medication. Residual limb pain and symptomatic neuromas are often not properly recognized by physicians explaining the varying prevalence in the literature. This systematic review and meta-analysis aim to provide a comprehensive overview of published literature on the prevalence of RLP and symptomatic neuroma after lower extremity amputation. Studies reporting the prevalence of RLP and symptomatic neuroma pain in patients who have had a lower extremity amputation published between 2000 and 2020 were identified in PubMed and Embase. Random-effects meta-analyses of proportions were performed to quantify the prevalence of RLP and symptomatic neuroma. Subgroups were identified and analysed. For RLP, the pooled prevalence was 59% (95% CI: 51-67). For symptomatic neuromas, the pooled prevalence was 15% (95% CI: 7-28). Residual limb pain subgroup analysis showed statistically significant higher prevalence in patients aged >50 years, follow-up >2 years, and in studies using a self-administered questionnaire for data collection. The prevalence of RLP and symptomatic neuroma in patients who have had a lower extremity amputation is 59% and 15%, respectively. Knowledge of their high prevalence may result in better awareness among physicians, in turn providing timely and adequate management. Abstract : Supplemental Digital Content is Available in the Text.